Family and higher education: developing a comprehensive framework of parents’ support and expectations of first-generation students - Flanagan-Bórquez, Andrea; Soriano-Soriano, Gabriel (Frontiers in Education, 2024)
Postsecondary institutions must help all students develop knowledge and skills to persist. Traditional approaches to first-generation students (FGS) have focused on describing the hindrances they experience during their undergraduate trajectories, defying their persistence. This qualitative study explores the experiences of FGS parents; specifically, the characteristics of their support and expectations toward FGS . Semi-structured individual interviews were conducted with 25 FGS parents from diverse Chilean universities. The data collected were analyzed through an inductive process, which included describing, classifying, and interpreting data into categories and themes. The results show that the motivation of families lies in the symbolism that they ascribe to higher education, deploying various modes of family support and resources to ensure that students complete their studies and attain a degree. This process is tailored to meet the initial expectations of FGS performance at university, which typically frame the type of support the family may provide. Postsecondary institutions and policymakers can use this study to develop future policies and practices that include FGS parents' perspective, expectations and characteristics of support, articulating these with academic culture, FGS's trajectories and own expectations to reduce inequality and promote retention.